KEKUATAN PEMBUKTIAN SAKSI DE AUDITU DALAM PERSPEKTIF HUKUM ACARA PIDANA DI INDONESIA - SUKMAN SUKMAN (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACT The purpose of this study is to find out how the criminal procedural law regulates de auditu witnesses and how the strength of binding the de auditu witness statements in the trial. The method used is normative juridical. Thus, the arrangement of evidence in the Criminal Procedure Code is regulated in a limited manner. This means that other evidence may not be used in terms of proving, other than those rQegulated by the law itself. The various types of evidence determined by the Criminal Procedure Code, namely witness statements, expert statements, letters, instructions and statements of the defendant. During the trial and during the evidentiary process, the judge must look at the five pieces of evidence to determine the truth of the crime being examined. After the decision of the Constitutional Court No. 65/PUU-VIII/2010 and several Supreme Court decisions which have implications for the expansion of the meaning of witnesses. Several decisions of the Supreme Court accepted the testimony of de auditu witnesses as witnesses on the grounds that many crime victims were unable to present evidence to prove the crime that had occurred to them because of insufficient evidence.Keywords: evidence, witness evidence, de auditu witness ABSTRAK Tujuan penelitian ini untuk mengetahui bagaimana hukum acara pidana mengatur tentang saksi de auditu dan bagaimana kekuatan mengikat keterangan saksi de auditu dalam persidangan. Metode yang digunakan adalah yuridis normatif. Dengan demikian, pengaturan alat bukti pada KUHAP diatur secara limitatif. Artinya, alat bukti yang lain tidak boleh dipakai dalam hal membuktikan, selain yang diatur oleh Undang-undang sendiri. Adapun macam-macam alat bukti yang ditentukan KUHAP, yaitu keterangan saksi, keterangan ahli, surat, petunjuk dan keterangan terdakwa. Ketika persidangan dan pada saat proses pembuktian hakim harus melihat kelima alat bukti tersebut untuk menentukan kebenaran dari tindak pidana yang sedang diperiksa. Setelah putusan MK No 65/PUU-VIII/2010 dan beberapa putusan Mahkamah Agung yang berimplikasi pada perluasan makna saksi. Beberapa putusan Mahkamah Agung menerima keterangan saksi de auditu sebagai saksi dengan alasan banyak korban kejahatan yang tidak mampu menghadirkan alat bukti untuk membuktikan tindak pidana yang terjadi pada dirinya karena terkendala alat bukti yang tidak cukup.Kata kunci: pembuktian, alat bukti saksi, saksi de auditu